Letter: higher severe outcomes among Helicobacter pylori‐related lean patients with non‐alcoholic fatty liver disease and metabolic comorbidities. Issue 10 (24th April 2023) - Kountouras, Jannis; Papaefthymiou, Apostolis; Polyzos, Stergios A.; Kazakos, Evangelos; Tzilves, Dimitrios; Touloumtzi, Maria; Chatzopoulos, Dimitrios; Tzitiridou‐Chatzopoulou, Maria; Liatsos, Christos; Zavos, Christos; Kavaliotis, John; Kulaksiz, Hasan; et al.
LINKED CONTENT: This article is linked to Wijarnpreecha et al paper. To view this article, visit https://doi.org/10.1111/apt.17424 .